CD38 Deficiency Alleviates D-Galactose-Induced Myocardial Cell Senescence Through NAD+/Sirt1 Signaling Pathway - Wang, Ling-Fang; Cao, Qing; Wen, Ke; Xiao, Yun-Fei; Chen, Ting-Tao; Guan, Xiao-Hui; Liu, Yu; Zuo, Li; Qian, Yi-Song; Deng, Ke-Yu; Xin, Hong-Bo (Frontiers in Physiology, 2019)
Our previous research showed that CD38 played vital roles in Ang-II induced hypertrophy and high fat diet induced heart injury. However, the role of CD38 in heart aging is still unknown. In the present study, we reported that CD38 knockdown significantly protected cardiomyocytes from D-galactose (D-gal)-induced cellular senescence. Cellular senescence was evaluated by 𝛽-galactosidase staining, the expressions of genes closely related to aging including p16 and p21, and the ROS production, MDA content and the expressions of oxidant stress related genes were examined by biochemical analysis, Western blot and QPCR. Our results showed that the expression of CD38 was increased in H9c2 cells after D-gal treatment and the expressions of NAMPT and Sirt1 were downregulated in heart tissue from old mice. CD38 knockdown significantly reduced the number of SA-𝛽-gal-positive cells and the expressions of p16 and p21 in H9c2 cells with or without D-gal treatment. The acetylation level of total protein was decreased in CD38 knockdown group, but the expression of Sirt3 was increased in CD38 knockdown group treated with D-gal. In addition, knockdown of CD38 significantly attenuated D-gal induced ROS production, MDA content and NOX4 expression in the cells. Furthermore, NAD+ supplementation reduced D-gal induced cellular senescence, ROS production and MDA content. The expression of SOD2 was increased and the NOX4 expression was decreased in H9c2 cells after NAD+ supplementation. Taken together, our results demonstrated that CD38 knockdown alleviated D-gal induced cell senescence and oxidative stress via NAD+/Sirt signaling pathway.